Affordability Level and Determinants of Low-Cost Home Ownership in the Federal Territory of Kuala Lumpur - Chew, Geok Luan (1989)
The provision of housing for low-income population has been a key issue in Malaysia. With the rapid rate of urbanisation in recent years, housing problems especially for the urban poor have become even more acute. To understand some underlying factors, the present work is an attempt to study the determinants which affect home ownership rate by low-income households and the affordability level of such households in the Federal Territory of Kuala Lumpur. Ordinary least squares and logit analysis are employed in the analysis of home ownership while the functional form of a Cj/Yi is used in evaluating affordability where 'a' is the proportion a household is willing to spend on housing; Cj is the housing cost associated with a given level of housing service, j; and Yi is the monthly income of a household at the ith percentile income distribution. Home ownership rate of the Federal Territory's low-income households is largely explained by income and the household head being Chinese. There is no difference between male and female-headed households towards home ownership; so is between public and private sector employees. Household size also does not exert much impact. On affordability issues, the low-income households of the Federal Territory on the average are able to spend about 18 percent of their income on housing cost. The present bank ruling of having one-third of one's monthly income as monthly housing installment has in fact induced many poor households to spend beyond their means. The market price of a low-cost house at M $25,000 is still unaffordable to a majority of the poor households. For a housing programme to be successful , the project design should be one that reflects the true willingness to pay by house seekers.